Climate Change, Gender and Media in Nigeria: Mainstreaming Gender in Climate Change Reporting - Funmi Falobi; Margaret Solo-Anaeto; Joseph Ifeoluwa Joy; Abdullahi Aliyu Maiwada (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
Climate change represents one of the most pressing global challenges, with far-reaching impacts across social, economic, and environmental systems. However, its effects are not evenly distributed, as existing inequalities shape differential vulnerabilities among populations. This paper interrogates the gendered dimensions of climate change, arguing that women and marginalised groups particularly in developing countries, experience disproportionate impacts due to entrenched socio-economic, cultural, and political disparities. Based on secondary data from the existing literature, the study highlights how climate change exacerbates challenges related to health, food security, water access, livelihoods, education, and exposure to violence, thereby reinforcing gender inequality. Anchored in framing theory, the paper analyses how media representations influence perception, agenda-setting, and policy prioritisation. It argues that the media serves as a powerful agent in raising awareness, amplifying marginalised voices, and promoting gender-sensitive narratives that can drive inclusive climate action. Through illustrative case studies from Nigerian print media, the paper demonstrates emerging efforts and best practices in mainstreaming gender into climate reporting, while also identifying gaps in representation and depth of coverage. The paper concludes that effective climate action requires the integration of gender perspectives into communication, policy, and practice.